Gene expression profiling of pulmonary neuroendocrine neoplasms: A comprehensive overview. (2015) - Swarts, Dorian R.A.; Ramaekers, Frans C.S.; Speel, Ernst J.M.
Abstract: Neuroendocrine neoplasms (NENs) of the lung comprise a heterogeneous group, including small cell lung cancer (SCLC), large cell neuroendocrine carcinoma and pulmonary carcinoids. To unravel their molecular biology, microarray studies have been conducted that provided lists of differentially expressed genes between lung NENs on the one hand and normal tissue and/or non-SCLCs on the other. However, the majority of studies paid little attention to the functions of candidates and their potency as diagnostic markers and/or therapeutic targets. Furthermore, at a first glance, only limited overlap was seen amongst these individual studies concerning differentially expressed transcripts. By combining all originally published gene expression profiling studies on lung NENs, and by re-evaluating differentially expressed genes, we were able to identify major factors involved in lung NEN carcinogenesis. Thirty-three genes were found to be frequently deregulated in multiple studies. Amongst these are neuroendocrine-specific factors, including ASH1, INSM1, and ISL1 and genes involved in neuronal differentiation and neurite outgrowth such as DCX and NCAM1 . Also, multiple factors were involved in cell cycle progression, including members of the mitotic spindle checkpoint complex, and the regulated secretory pathway, e.g. CHGA and CHGB and CPE . For several of these candidates we propose possible functions in lung NEN carcinogenesis as well as potential roles in diagnosis and as targets for novel therapies. This review elucidates potential genes of interest in pulmonary NENs on basis of the present expression profiling literature. We advocate that a selection of the identified candidates should be examined in depth for their clinical application. Highlights: Published gene expression studies on lung neuroendocrine neoplasms re-evaluated. Focus on important factors reported by multiple studies. Many genes involved in neuroendocrine development and cell cycle progression. Potential roles of these factors in diagnosis and as therapeutic targets proposed.